The parasitoid wasp Eruga unilabiana Pádua & Sobczak, sp. nov. (Hymenoptera: Ichneumonidae) induces behavioral modification in its spider host - Sobczak, Jober Fernando; Pádua, Diego Galvão; Costa, Letícia F.A.; Carvalho, João L.V.R.; Ferreira, João P.S.; Sobczak, Jullyana Cristina Magalhães Silva Moura; Messas, Y. F. (Entomological Science, 2018)
Some polysphinctine parasitoid wasps can alter the web building behavior of their host spiders. In this paper, we describe and illustrate a new species Eruga unilabiana sp. nov. and report for the first time, to the best of our knowledge, the interaction between this parasitic wasp and the linyphiid spider Dubiaranea sp. We investigated the wasp's host selection, development, and manipulation of host behavior. We found that most of the parasitized spiders were intermediate-sized adult females that probably provide sufficient resources for parasitoid larvae and are less vulnerable for parasitoid females than larger host individuals at attack. The cocoon web of Dubiaranea sp. consists of a complex three-dimensional tangle structure with several non-stick radial lines that converge at the cocoon. In addition, E. unilabiana individuals construct their cocoons horizontally, which differ from cocoons of the majority of polysphinctine wasps. This study provides important information and discussion to further understand the evolution of parasitoid wasp–spider interactions. © 2017 The Entomological Society of Japan